Notary's Authority to Make a Deed of Power of Attorney for a Credit Agreement Without the Consent of the Owner of the Land Rights Certificate - Agustin, Dwi; Rochim, Abdul; Sunardi, Sunardi (Journal of Law, Politic and Humanities, 2025)
This study aims to examine the authority of notaries in making power of attorney deeds in credit agreements without the consent of the land title certificate owner, along with its legal consequences, and legal protection against misuse of power of attorney deeds for additional credit agreements made without the knowledge of the certificate owner. This study is a type of normative legal research using a statutory approach and a conceptual approach. The legal materials used include primary legal materials, secondary legal materials, and tertiary legal materials. The results of this study are: first, Notaries do not have the authority to make power of attorney deeds for credit agreements without the consent of the land title certificate owner; second, the legal consequences for the owner of the land title certificate if there is a misuse of the power of attorney for credit agreements without his/her consent can be in the form of material or immaterial losses; and third, the form of legal protection for the owner of the land title certificate for the misuse of the power of attorney for credit agreements without his/her consent can be taken through legal efforts in the form of: civil lawsuits for compensation, criminal charges on the basis of unlawful acts, and/or complaints to the Notary Supervisory Board for violations of the notary's code of ethics in making power of attorney for credit agreements without the consent of the owner of the land title certificate.